2021
DOI: 10.1099/mgen.0.000505
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenomic analyses of Mycobacterium microti, an ESX-1-deleted member of the Mycobacterium tuberculosis complex causing disease in various hosts

Abstract: Mycobacterium microti is an animal-adapted member of the Mycobacterium tuberculosis complex (MTBC), which was originally isolated from voles, but has more recently also been isolated from other selected mammalian hosts, including occasionally from humans. Here, we have generated and analysed the complete genome sequences of five representative vole and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 105 publications
(232 reference statements)
5
8
0
Order By: Relevance
“…The results also show that M. tuberculosis and M. bovis strains, representing the globally most widely distributed pathogens among the MTBC members, apparently lack the ability to act as recipients, whereas they can still act as donors. This scenario is in agreement with the stable clonal phylogeographic lineages that are formed within the MTBC, in which the vertical transfer of genes, mutations, and deletions defines the genotypes of the daughter generations and where loss-of-function mutations cannot be repaired by HGT (25,27,54,55).…”
Section: Kansasii Stb-d Nosupporting
confidence: 81%
See 2 more Smart Citations
“…The results also show that M. tuberculosis and M. bovis strains, representing the globally most widely distributed pathogens among the MTBC members, apparently lack the ability to act as recipients, whereas they can still act as donors. This scenario is in agreement with the stable clonal phylogeographic lineages that are formed within the MTBC, in which the vertical transfer of genes, mutations, and deletions defines the genotypes of the daughter generations and where loss-of-function mutations cannot be repaired by HGT (25,27,54,55).…”
Section: Kansasii Stb-d Nosupporting
confidence: 81%
“…Complete read pairs were then de novo assembled using SPAdes v3.10.1 (85) (parameters --careful, -k 21,33,55 for HiSeq reads or -k 21,33,55,77 for NextSeq reads, and --phred-offset 33). The contigs thus generated were finally organized using MeDuSa v1.6 (86) (default parameters) and compared to the corresponding reference genome of each donor or recipient strain (see Table S4 in the supplemental material for details) (25,28,32,45,47,(87)(88)(89).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the genome of Mtb (Cole et al, 1998) encodes five ESX T7SS (ESX-1 to ESX-5), in the current review, we will mainly focus on the ESX-1 system, which is absent from live attenuated vaccine strains of Mycobacterium bovis BCG (BCG) (Hsu et al, 2003;Pym, Brodin, Brosch, Huerre, & Cole, 2002) and Mycobacterium microti M.P. Prague (Orgeur et al, 2021), and its role in processes leading to induction of phagosomal rupture. The most well-known ESX-1 substrate in this context is EsxA (also known as Early Secretory Antigenic Target of 6 kDa, ESAT-6) Sorensen, Nagai, Houen, Andersen, & Andersen, 1995), which is required for full virulence of Mtb and the related fish pathogen Mycobacterium marinum (reviewed in [Groschel et al, 2016] and [Chirakos et al, 2020], respectively).…”
Section: Take Awaymentioning
confidence: 99%
“…Recently, it has been shown that the ppe38-71 operon, specifically the PPE38 protein, is involved in mediating secretion of both these important subfamilies and when deleted detectable secretion is abolished (13). More recent follow up studies conducted in M. africanum and M. microti demonstrated a lack of PE-PGRS secretion in the presence of an intact ppe38-71 operon and ESX-5 secretion system (14,15). While it is clear that the ppe38-ppe71 operon is involved in PE-PGRS secretion, this phenotype can be present in other mycobacteria, driven by an independent and currently unknown mechanism.…”
Section: Introductionmentioning
confidence: 99%